A bibliometric analysis of chronic subdural hematoma since the twenty-first century - Chen, Rundong; Wei, Yanpeng; Xu, Xiaolong; Zhang, Renkun; Tan, Yuhao; Zhang, Guanghao; Yin, Hongwei; Dai, Dongwei; Li, Qiang; Zhao, Rui; Huang, Qinghai; Xu, Yi; et al. (European Journal of Medical Research, 2022)
Chronic subdural hematoma (CSDH) is a common disease that forms between the dura and arachnoid membranes of the brain. With the development of medications and surgery, significant progress has been made in the diagnosis and treatment of CSDH. However, there is no comprehensive analysis available on CSDH-related studies published in the literature. This study aimed to collect and analyze CSDH-related studies published since the twenty-first century using bibliometric analysis and to summarize the current status of research in this field for the sake of providing systematic data for further study of CSDH. CSDH-related studies were searched in the Web of Science Core Collection (WoSCC) database using the Medical Subject Heading (MeSH) term 'chronic subdural hematoma'. Data analysis and visualization were performed by R and CiteSpace software. This study retrieved 1424 CSDH-related articles published since the beginning of the twenty-first century. There was a general increase in both the number of published articles and the mean number of citations. The authors, institutions and journals that contributed the most to the field of CSDH were Jianning Zhang, Tianjin Medical University, and world neurosurgery, respectively. The reference co-citation network identified 13 clusters with significant modularity Q scores and silhouette scores (Q = 0.7124, S = 0.8536). The major research categories were (1) evolution of the therapeutic method and (2) the etiology and pathology of CSDH. Keyword analysis revealed that 'middle meningeal artery embolization' was the latest burst keyword. This study identified the most influential countries, authors, institutions and journals contributing to CSDH research and discussed the hotspots and the latest subjects of CSDH research.